Between Memory and Trajectory: Gendered Literary Narratives of Javanese Diaspora in New Caledonia - Wening Udasmoro; Setiadi Setiadi; Aprillia Firmonasari (International Journal of Interreligious and Intercultural Studies, 2022)
The purpose of this research is to explore the memory and the trajectory of the Javanese diaspora on the novels written by two female authors of Javanese descent in New Caledonia using a gender perspective. The Javanese diaspora in New Caledonia is a community that has left their homeland (Java) to start a new life in their destination land (New Caledonia) since 1896. They are descendants of the contract coolies (laborers) sent by the Dutch colonial government who controlled the Dutch Indies, including Java, at the request of French colonial government. The delivery of contract coolies was based on an agreement called the “Koeli Ordonatie” which had become a legal regulation and was implemented since the 1880s. It was a regulation signed by the Governor-General of the Netherlands Number 138 whose purpose was to fid unskilled laborers willing to work in the Dutch colonies, especially in the plantations and mining. The coolies, especially from Java, were mostly used as manual laborers in various parts of Dutch colonies, such as in Suriname. Seeing that this Dutch policy brought positive results for the exploitation of natural resources in the Dutch colonies, the French colonial government asked the help from the Dutch colonial government to recruit the laborers to be sent to French colonial region, New Caledonia.